The wrongful convictions reader - Covey, Russell D.; Beety, Valena (Carolina Academic Press, 2019)
Prologue to wrongful convictions -- Defining innocence and miscarriages of justice -- Overview of the causes of wrongful convictions -- The innocence "myth" and the costs of preventing wrongful convictions -- Eyewitness misidentifications -- False confessions -- Scientific standards, statistical evidence, and the future of forensic science -- DNA and junk science -- Informants and snitches -- Police and prosecutorial misconduct -- Incompetent lawyering -- Cognitive bias and tunnel vision -- Guilty pleas, pretrial procedure, and innocence -- Appellate and post-conviction review of innocence -- Innocence, equitable tolling, and procedural default -- Intersections: race, gender, sexual orientation and innocence -- Reconsidering innocence: rethinking causes and addressing consequences